Multidimensional poverty and its discontents - Alkire, S (Oxford Poverty & Human Development Initiative (OPHI), 2010)
This paper identifies a set of research questions and debates which relate to a general approach to multidimensional poverty measurement, or to one particular class of measures (Alkire & Foster), or to one application of one of these measures, the Multidimensional Poverty Index (MPI) 2010.